Grating-Based X-Ray Computed Tomography for Improved Contrast on a Heterogeneous Geomaterial - Moore, Rachael Leigh; Patera, Alessandra; Bonnin, Anne; Ménez, Bénédicte (Frontiers in Earth Science, 2022)
Phase-contrast X-ray imaging has shown its potential to capture at micrometric scale and in three dimensions (3D), the structure and deformation of poorly-absorbing soft materials such as polymers and biological structures. When composed of constituents that attenuate X-rays differently, heterogeneous hard materials are often well resolved in 3D using absorption-based X-ray computed tomography (CT) techniques. As a result, phase-contrast techniques have been less frequently used to image such materials. However, many geomaterials contain similarly X-ray attenuating constituents, thereby complicating the use of absorption-based X-ray CT methods. Here we present the innovative use of grating-based synchrotron radiation computed tomography, a phase-sensitive technique, in order to better identify the distribution of constituents within geomaterials. We show that this approach enhances the contrast between similarly X-ray absorbing constituents, and can be used to identify spatially small structures such as pores or mineral grains that are typically poorly resolved with conventional absorption-based X-ray CT.